Preparation method and application of Ag-modified MOFs@COFs composite photocatalyst
Through the preparation of Ag-modified MOFs@COFs composite photocatalyst, the existing photocatalyst degradation capacity and complex preparation process are solved, and the efficient degradation of oleracycin and simplified preparation process is achieved, and the photocatalytic performance and utilization are improved.
Patent Information
- Application Number
- CN202410859449.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing photocatalyst has limited degradation capacity and low light utilization rate. The preparation methods and processes of existing MOFs and COFs composite photocatalysts are cumbersome and the synthesis conditions are strict, making it difficult to accurately regulate the catalytic performance.
The preparation method of Ag-modified MOFs@COFs composite photocatalyst is used to prepare MOFs by hydrothermal reaction, and then photoreduction reaction is carried out under light conditions to synthesize Ag-modified MOFs, combined with COFs to form a composite photocatalyst with a rod-like structure, using a large specific surface area and enrich pore structure to improve photocatalytic performance.
It achieves higher light utilization and catalytic performance than traditional semiconductor photocatalysts, can effectively degrade oleracycin, and maintain high efficiency after multiple cycles, simplifies the preparation process, overcomes the cumbersome and harsh synthesis conditions of the process .
Smart Images

Figure CN118847220B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalyst preparation, and in particular to a preparation method and application of an Ag-modified MOFs@COFs composite photocatalyst. Background Art
[0002] Oxytetracycline hydrochloride (OTC) is a broad-spectrum antibiotic with high water solubility, complex structure, high stability, and difficulty in natural degradation. Its concentration range for wastewater removal is usually 0.24-15.1 mg / L. At present, due to the huge output of aquaculture, a large amount of aquaculture wastewater is generated. Excessive aquaculture wastewater poses a great threat to the ecological environment. The accumulation of OTC in wastewater in water bodies leads to serious water pollution problems and the growth of drug-resistant harmful bacteria, which seriously affects the aquatic ecosystem. If this phenomenon is allowed to develop, it will eventually affect human health. Therefore, there is an urgent need to construct an efficient method for removing OTC to reduce the negative impact of OTC on aquatic ecosystems and public health.
[0003] Common methods for degrading antibiotics include biological methods, physical adsorption methods, chemical oxidation methods, etc. Among them, the chemical oxidation method uses the strong oxidizing property of photocatalysts to achieve the degradation and transformation of organic pollutants. This method is more efficient and thorough because it can effectively degrade all organic pollutants including antibiotics such as oxytetracycline. However, the commonly used semiconductor photocatalysts have limited degradation capabilities, low light utilization, and low photocatalytic efficiency. In addition, in order to improve the catalytic efficiency of photocatalysts, the prior art proposes to combine organic metal frameworks (MOFs) and covalent organic frameworks (COFs) to prepare photocatalysts, but the existing preparation methods are cumbersome, the synthesis conditions are harsh, and it is difficult to accurately control the performance of the photocatalyst. Therefore, the overall catalytic efficiency of the photocatalyst is still not high.
[0004] In view of this, it is necessary to design an improved preparation method and application of Ag-modified MOFs@COFs composite photocatalyst to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of an Ag-modified MOFs@COFs composite photocatalyst.
[0006] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing an Ag-modified MOFs@COFs composite photocatalyst, comprising the following steps:
[0007] S1. Dissolve zirconium oxychloride octahydrate and 4-carboxyphenylporphyrin in an organic solvent, carry out hydrothermal reaction at 130-150° C. for 48-72 hours in the presence of formic acid, and then wash and dry to obtain PCN-222;
[0008] S2, dispersing the PCN-222 obtained in step S1 in water to obtain a PCN-222 dispersion; adding a silver nitrate solution to the PCN-222 dispersion, performing a photoreduction reaction under light conditions, and finally obtaining PCN-222 / Ag;
[0009] S3, adding terephthalaldehyde and 1,3,5-tris(4-aminophenyl)benzene to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding acetic acid, reacting under stirring conditions, and drying to obtain a covalent organic framework TAPB-PDA; adding different proportions of raw materials of the covalent organic framework TAPB-PDA and PCN-222 / Ag obtained in step S2 to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding different proportions of acetic acid, and after the reaction is completed, washing and drying to obtain PCN-222 / Ag / COF.
[0010] Preferably, in step S2, the concentration of the PCN-222 dispersion is 2-3 g / L, the concentration of the silver nitrate solution is 0.1-0.2 mmol / L, the mass ratio of the PCN-222 content in the PCN-222 dispersion to the theoretical reduced Ag is 100:3; and the time of the photoreduction reaction is 3-4 h.
[0011] Preferably, in step S1, the organic solvent is N,N-dimethylformamide, and the ratio of the mass of zirconium oxychloride octahydrate, the mass of 4-carboxyphenylporphyrin, and the volume of the organic solvent is 37.5:6.5:10.
[0012] Preferably, in step S1, the concentration of formic acid is 17.5-18 mol / L, and the ratio of its added volume to the mass of zirconium oxychloride octahydrate is 7:37.5; the temperature of the drying process is 120-130°C, and the time is 48-72h.
[0013] Preferably, in step S3, the volume ratio of 1,4-dioxane to mesitylene in the mixed solution of 1,4-dioxane and mesitylene is 1:4; the ratio of the mass of terephthalaldehyde, the mass of 1,3,5-tris(4-aminophenyl)benzene to the volume of the mixed solution of 1,4-dioxane and mesitylene is 12:24:10.
[0014] Preferably, in step S3, the concentration of acetic acid is 0.5-0.6 mol / L; and the reaction time for preparing the covalent organic framework TAPB-PDA is 48-72 h.
[0015] Preferably, the mass ratio of the covalent organic framework TAPB-PDA, the mass of PCN-222 / Ag and the volume ratio of the mixed solution of 1,4-dioxane and mesitylene is 53.55:100:10; the reaction time is 48-72h, and the temperature is 25-30°C.
[0016] The Ag-modified MOFs@COFs composite photocatalyst prepared by the preparation method proposed in the present invention has a rod-like structure, the main axis of the crystal is a hexahedron, the length is 25.11-43.64 μm, the particle size is 25.11-43.64 μm, the specific surface area is 115.44-118.50 m2 / g, the average pore is 0.1105-0.1165 mL / g, and can be applied to the field of photocatalytic degradation of oxytetracycline.
[0017] The beneficial effects of the present invention are:
[0018] 1. The preparation method of the Ag-modified MOFs@COFs composite photocatalyst provided by the present invention comprises the following steps: first preparing MOFs and then sequentially synthesizing Ag and COFs in situ thereon, so as to give full play to the structural properties of MOFs and COFs, and finally obtaining an Ag-modified MOFs@COFs composite photocatalyst which has higher light utilization rate and catalytic performance than traditional semiconductor photocatalysts (TiO2, ZnO, etc.) and can be recycled.
[0019] 2. The preparation method of the Ag-modified MOFs@COFs composite photocatalyst provided by the present invention, by introducing MOFs and COFs with large specific surface area and rich pore structure, can not only utilize the two to adsorb and enrich the substances to be degraded, but also utilize the pore structure of the two to stabilize AgNPs, thereby avoiding the phenomenon of Ag NPs agglomeration in the preparation process and affecting the catalytic efficiency of the catalyst; secondly, the present invention also adjusts the addition amount of each raw material to accurately control the content and morphology of Ag, MOFs and COFs in the catalyst, and finally obtains a composite photocatalyst that can effectively degrade oxytetracycline, and after multiple degradations, the catalyst still shows a high catalytic efficiency.
[0020] 3. The preparation method of the Ag-modified MOFs@COFs composite photocatalyst provided by the present invention can be achieved at room temperature, overcoming the difficulties of the complicated process and harsh synthesis conditions of the in-situ synthesis of MOFs and COFs, and providing an effective preparation method for the preparation of MOFs and COFs composite photocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the composite photocatalyst prepared in Example 1 of the present invention;
[0022] Figure 2This is an EDS-mapping diagram of the composite photocatalyst prepared in Example 1 of the present invention;
[0023] Figure 3 This is the XRD diagram of the composite photocatalyst prepared in Example 1 of the present invention;
[0024] Figure 4 is the XRD pattern of pure COF;
[0025] Figure 5 This is a fluorescence lifetime diagram of the photocatalyst prepared in Example 1 of the present invention;
[0026] Figure 6 The electrochemical impedance diagrams of the photocatalysts prepared in Examples 1 to 3 of the present invention;
[0027] Figure 7 This is a photocatalyst photocurrent response diagram obtained in Example 1 of the present invention;
[0028] Figure 8 The degradation curve of oxytetracycline hydrochloride by photocatalysis
[0029] Fig. 9 The degradation curve of oxytetracycline hydrochloride by photocatalysis of the catalyst is shown;
[0030] Fig.10 It is the degradation curve diagram of oxytetracycline hydrochloride by photocatalysis of the catalyst;
[0031] Fig.11 This is the XRD diagram of the cyclic experiment of the catalyst photocatalysis on oxytetracycline hydrochloride;
[0032] Fig.12 This is an XPS graph of the composite photocatalyst prepared in Example 1 of the present invention;
[0033] Fig.13 Solid UV and band gap width diagram of the composite photocatalyst prepared in Example 1 of the present invention;
[0034] Fig.14 This is the MS graph of the composite photocatalyst prepared in Example 1 of the present invention;
[0035] Fig.15 This is a diagram showing the degradation mechanism of the composite photocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0038] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0039] The preparation method of the Ag-modified MOFs@COFs composite photocatalyst provided by the present invention comprises the following steps:
[0040] S1. Dissolve the zirconium source and 4-carboxyphenylporphyrin in an organic solvent, perform hydrothermal reaction at 130-150°C for 48-72h in the presence of formic acid, and then wash and dry to obtain PCN-222;
[0041] S2, dispersing the PCN-222 obtained in step S1 in water to obtain a PCN-222 dispersion; adding a silver nitrate solution to the PCN-222 dispersion, performing a photoreduction reaction under light conditions, and finally obtaining PCN-222 / Ag;
[0042] S3, adding terephthalaldehyde and 1,3,5-tris(4-aminophenyl)benzene to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding acetic acid, reacting under stirring, and drying to obtain a covalent organic framework TAPB-PDA; adding different proportions of the raw materials of the covalent organic framework TAPB-PDA and the PCN-222 / Ag obtained in step S2 to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding acetic acid, and after the reaction is completed, washing and drying to obtain PCN-222 / Ag / COF, wherein the ratio of the mass (mg) of zirconium oxychloride octahydrate, the mass (mg) of 4-carboxyphenylporphyrin, and the volume (mL) of the organic solvent is 37.5:6.5:10.
[0043] As an embodiment of the present invention, in step S1, the organic solvent is N,N-dimethylformamide (DMF), and the zirconium source is a zirconium-containing salt such as zirconium oxychloride octahydrate. In particular, in some embodiments, in order to make the various substances mixed evenly after adding formic acid, ultrasonic mixing can be used. Since the purpose of this process is to mix evenly, the ultrasonic time can be adjusted according to actual conditions, such as 30-45 minutes, which is not limited here.
[0044] As an embodiment of the present invention, in step S1, the added volume of formic acid is 7-8 mL, the concentration thereof is 17.5-18 mol / L, and the mass ratio of the added volume (mL) to the zirconium oxychloride octahydrate (mg) is 7:37.5.
[0045] As an embodiment of the present invention, in step S1, the washing process is carried out using DMF and acetone to remove the reactants adsorbed on the product; the temperature of the drying process is 60-70°C and the time is 6-12h.
[0046] As an embodiment of the present invention, in step S2, the concentration of the PCN-222 dispersion is 2.5-3 g / L, the concentration of the silver nitrate solution is 1.63-2.5 mg / mL, and the mass ratio of the PCN-222 content in the PCN-222 dispersion to the theoretical reduced Ag is 100: 3. It should be noted that the theoretical reduced Ag amount is the amount of Ag calculated after the reduction of silver nitrate according to the chemical equation.
[0047] As an embodiment of the present invention, in step S2, the photoreduction reaction time is 3-4 hours and the temperature is 25-30°C.
[0048] As an embodiment of the present invention, in step S3, the volume ratio of dioxane and mesitylene in the mixed solution of 1,4-dioxane and mesitylene is 4:1 (mL:mL), and the ratio of the mass (mg) of terephthalaldehyde, the mass (mg) of 1,3,5-tris(4-aminophenyl)benzene to the volume (mL) of the mixed solution of 1,4-dioxane and mesitylene is 12:24:10.
[0049] As an embodiment of the present invention, in step S3, acetic acid is added as a crystallization agent in an amount of 100-350 μm; acetic acid is added as a crystallization agent in an amount of 100-350 μm; the reaction time of the process for preparing the covalent organic framework TAPB-PDA is 48-72 h.
[0050] As an embodiment of the present invention, in step S3, the theoretical loading amount of the covalent organic framework TAPB-PDA is 33.25-53.55 mg, the added amount of PCN-222 / Ag is 90-100 mg, the added amount of 1,4-dioxane is 4-12 mL, and the added amount of mesitylene mixed solution is 1-3 mL.
[0051] As an embodiment of the present invention, in step S3, PCN-222 / Ag / COF is a rod-like structure, the main axis of the crystal is hexahedral, the length is 25.11-43.64 μm, the particle size is 25.11-43.64 μm, the specific surface area is 115.44-118.50 m2 / g, and the porosity is 0.1105-0.1165 mL / g.
[0052] In particular, the Ag-modified MOFs@COFs composite photocatalyst prepared by the method proposed in the present invention can be used as a photocatalyst, and is particularly suitable for the catalytic degradation of antibiotics such as oxytetracycline.
[0053] The preparation method and application of the Ag-modified MOFs@COFs composite photocatalyst of the present invention are further described below in conjunction with specific embodiments:
[0054] The reagents used in the embodiments of the present invention are all purchased from the market, and the sources of the specific reagents are as follows:
[0055]
[0056] Example 1
[0057] The present invention prepares an Ag-modified MOFs@COFs composite photocatalyst, and the preparation method thereof comprises the following steps:
[0058] S1. Dissolve 37.5 mg of zirconium oxychloride octahydrate and 6.5 mg of 4-carboxyphenylporphyrin in 10 mL of DMF, and dissolve all solids by ultrasonication for 30 min. Add 7 mL of formic acid to the above solution, and hydrothermally react at 130° C. for 72 h. After the reaction is completed, wait for the product to cool to room temperature, ultrasonically wash the product with DMF, centrifuge the product until the supernatant is colorless and transparent, and then wash it with acetone for 3-5 times to ensure that the product does not contain DMF. Then, vacuum dry the washed product at 120° C. for 12 h to obtain PCN-222 with a smooth surface and hexagonal shape.
[0059] S2, 100 mg of PCN-222 prepared in step S1 was dispersed in 30 mL of water, and ultrasonicated for 10 min to prepare a PCN-222 dispersion; 2.90 mL of silver nitrate solution with a silver content of 1.63 mg / mL was added to the PCN-222 dispersion, stirred for 30 min, and irradiated with a xenon lamp for 3 h for photoreduction reaction. After the reaction was completed, the mixture was washed with ultrapure water and ethanol for 3-5 times, respectively, to finally prepare PCN-222 / Ag 3.0 (Ag mass percentage is 3.00%); In this step, the Ag content of the composite process can be regulated by adjusting the amount of silver nitrate solution added. When the added volume is 1.00 mL, PCN-222 / Ag is obtained. 1.0(Ag mass percentage is 1.03%), when the added volume is 4.85mL, PCN-222 / Ag is obtained 5.0 (Ag mass percentage is 5.02%);
[0060] S3, 40 mg of terephthalaldehyde and 80 mg of 1,3,5-tris(4-aminophenyl)benzene were added to 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1, mixed evenly, and then 1 mL of acetic acid was added, and the mixture was reacted under magnetic stirring for 72 h. After the reaction was completed, the mixture was vacuum dried at 70 ° C for 12 h to obtain a covalent organic framework TAPB-PDA; 21 mg of phthalaldehyde (PDA), 42 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 100 mg of PCN-222 / Ag prepared in step S2 were added. 3.0 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1 was added, stirred for 1 h to mix evenly, and then 350 μL of acetic acid was added. The mixture was stirred continuously at 25 ° C for 3 days. After the reaction was completed, the precipitate was collected and washed with tetrahydrofuran and ethanol for 3-5 times, and dried at 70 ° C under vacuum conditions for 12 h. The product was named PCN-222 / Ag 3.0 / COF2. According to the BET test, the specific surface area of the composite materials prepared in Examples 3 is 115.44-118.50 m2 / g, and the porosity is 0.1105-0.1165 mL / g; in addition, the length of the composite materials is 25.11-43.64 μm, and the particle size is 25.11-43.64 μm.
[0061] The SEM image of the composite photocatalyst prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the microscopic morphology of the composite photocatalyst is a rod-like structure, and its crystal main axis is a hexahedron; the EDS-mapping diagram of the composite photocatalyst is shown in Figure 2 As shown in the figure, the results show that Ag, MOF, and COF are successfully composited together; the XRD diagram is shown in Figure 3 As shown, the results indicate that the composite photocatalyst was successfully prepared.
[0062] The XRD pattern of pure COF is as follows Figure 4 As shown; the photoelectric properties of the samples were tested using UV-visible spectroscopy, and the results are shown Figure 5-7 As shown in Figure 2, the photocurrent response and electrochemical impedance spectroscopy (EIS) analysis of the separation ability of photogenerated electron-hole pairs were measured in 0.5 mol / L sodium sulfate electrolyte. 3.0 τ of COF2 samples avgThe values were calculated to be 6.11, 6.45 and 6.59 ns, respectively. The results show that the composite photocatalyst has the ability to prolong the lifetime of photoinduced carriers. Among them, the average lifetime of the sample (τ avg ) The calculation formula for the analysis is τ=(B1t1 2 +B2τ2 2 ) / (B1τ1+B2τ2).
[0063] Table 1 PCN-222, COF and PCN-222 / Ag 3.0 / Fluorescence lifetime of COF2
[0064]
[0065] Example 2
[0066] The present invention prepares an Ag-modified MOFs@COFs composite photocatalyst, and the preparation method thereof comprises the following steps:
[0067] S1. Dissolve 37.5 mg of zirconium oxychloride octahydrate and 6.5 mg of 4-carboxyphenylporphyrin in 10 mL of DMF, and sonicate for 30 min to dissolve all solids; add 7 mL of formic acid to the above solution, and hydrothermally react at 130° C. for 72 h. After the reaction is completed, wait for the product to cool to room temperature, and then use DMF to sonicate and centrifuge to wash the product until the supernatant is colorless and transparent, and then wash with acetone 3-5 times to ensure that the product does not contain DMF; then vacuum dry the washed product at 120° C. for 12 h to obtain PCN-222;
[0068] S2, 100 mg of PCN-222 prepared in step S1 was dispersed in 30 mL of water, and ultrasonicated for 10 min to prepare a PCN-222 dispersion; 2.90 mL of silver nitrate solution with a silver content of 1.63 mg / mL was added to the PCN-222 dispersion, stirred for 30 min, and irradiated with a xenon lamp for 3 h for photoreduction reaction. After the reaction was completed, the mixture was washed with ultrapure water and ethanol for 3-5 times, respectively, to finally prepare PCN-222 / Ag 3.0 (Theoretical mass percentage of Ag is 3.00);
[0069] S3, 40 mg of terephthalaldehyde and 80 mg of 1,3,5-tris(4-aminophenyl)benzene were added to 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1, mixed evenly, added to 1 mL of acetic acid, reacted under magnetic stirring for 72 h, and after the reaction was completed, vacuum dried at 70 ° C for 12 h to obtain a covalent organic framework TAPB-PDA; 15 mg of phthalaldehyde (PDA) and 30 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) were added, followed by 250 μL of acetic acid, and then 100 mg of PCN-222 / Ag prepared in step S2 was added 3.0 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1 was added, stirred for 1 h to mix evenly, and then stirred continuously for 3 days at 25 ° C. After the reaction was completed, the precipitate was collected and washed with tetrahydrofuran and ethanol for 3-5 times, and dried at 70 ° C under vacuum conditions for 12 h. The product was named PCN-222 / Ag 3.0 / COF1.
[0070] Example 3
[0071] The present invention prepares an Ag-modified MOFs@COFs composite photocatalyst, and the preparation method thereof comprises the following steps:
[0072] S1. Dissolve 37.5 mg of zirconium oxychloride octahydrate and 6.5 mg of 4-carboxyphenylporphyrin in 10 mL of DMF, and sonicate for 30 min to dissolve all solids; add 7 mL of formic acid to the above solution, and hydrothermally react at 130° C. for 72 h. After the reaction is completed, wait for the product to cool to room temperature, and then use DMF to sonicate and centrifuge to wash the product until the supernatant is colorless and transparent, and then wash with acetone 3-5 times to ensure that the product does not contain DMF; then vacuum dry the washed product at 120° C. for 12 h to obtain PCN-222;
[0073] S2, 100 mg of PCN-222 prepared in step S1 was dispersed in 30 mL of water, and ultrasonicated for 10 min to prepare a PCN-222 dispersion; 2.90 mL of silver nitrate solution with a silver content of 1.63 mg / mL was added to the PCN-222 dispersion, stirred for 30 min, and irradiated with a xenon lamp for 3 h for photoreduction reaction. After the reaction was completed, the mixture was washed with ultrapure water and ethanol for 3-5 times, respectively, to finally prepare PCN-222 / Ag 3.0 (Theoretical mass percentage of Ag is 3.00);
[0074] S3, 40 mg of terephthalaldehyde and 80 mg of 1,3,5-tris(4-aminophenyl)benzene were added to 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1, mixed evenly, added to 1 mL of acetic acid, reacted under magnetic stirring for 72 h, and after the reaction was completed, vacuum dried at 70 ° C for 12 h to obtain a covalent organic framework TAPB-PDA; 27 mg of phthalaldehyde (PDA) and 54 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) were added, followed by 450 μL of acetic acid, and then 100 mg of PCN-222 / Ag prepared in step S2 was added 3.0 10 mL of a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1 was added, stirred for 1 h to mix evenly, and then stirred continuously for 3 days at 25 ° C. After the reaction was completed, the precipitate was collected and washed with tetrahydrofuran and ethanol for 3-5 times, and dried at 70 ° C under vacuum conditions for 12 h. The product was named PCN-222 / Ag 3.0 / COF3.
[0075] In order to explore the photocatalytic degradation effect of the Ag-modified MOFs@COFs composite photocatalyst prepared in Examples 1 to 3 on oxytetracycline, the test process was carried out as follows: 5 mg of the composite photocatalyst was added to 100 mL of oxytetracycline solution with a concentration of 20 mg / mL, and the catalyst was evenly dispersed in the oxytetracycline solution by ultrasound. The dark adsorption was carried out by magnetic stirring for 40 minutes until the dark adsorption equilibrium was reached; the degradation system was transferred to a xenon lamp environment and photocatalyzed under the irradiation of a xenon lamp. Every 15 minutes, 3 mL of the solution was taken out, and the solid catalyst was filtered out, and its absorbance was measured at 354 nm. The removal rates of the catalysts prepared in Examples 1 to 3 for oxytetracycline were 89.38%, 77.18%, and 67.92%, respectively, while the removal rates of PCN-222, Ag NPs, and COF / Ag for oxytetracycline were 63.54%, 9.01%, and 68%, respectively.
[0076] The photodegradation curve of the sample is shown in Figure 8 As shown in Figure 2, oxytetracycline cannot be naturally degraded without a catalyst, and PCN-222, Ag NPs, and Ag 1.0 / PCN-222、Ag 3.0 / PCN-222、Ag 5.0 The degradation rates of OTC by PCN-222 / Ag and COF were 63.54%, 9.01%, 70.06%, 76.67%, 70.00% and 50.07%, respectively. Although PCN-222 has significant adsorption capacity and a wide visible light absorption range, its photodegradation efficiency is relatively low due to the rapid recombination of photogenerated electrons and holes on its surface. 3.0 / COF1、PCN-222 / Ag 3.0 / COF2 and PCN-222 / Ag 3.0 The degradation light removal rates of OTC by AgNPs / COF3 were 77.18%, 89.38% and 67.92%, respectively. The results showed that the degradation rate increased with the increase of Ag NPs and COF content; however, when the mass ratio of AgNPs exceeded 3wt% and COF was excessive, the degradation rate decreased ( Fig. 9 ), which may be due to the fact that the overly thick shell limits the utilization of light; compared with PCN-222, COF and pure Ag, the core-shell photodecomposition body PCN-222 / Ag 3.0 / COF2 has a high photocatalytic degradation efficiency, which may be due to the core-shell structure of PCN-222 / Ag 3.0 / COF2, which can accelerate the separation of photoinduced electrons and holes and help improve the efficiency of photocatalytic degradation.
[0077] The removal rate of oxytetracycline by the composite photocatalyst during the cyclic catalytic process is as follows Fig.10 As shown in the figure, the results show that the composite catalyst still has a high photodegradation efficiency after multiple cycles; in order to explore the photostability and chemical stability of the composite catalyst during the photocatalytic process, the XRD patterns of the composite photocatalyst before and after photocatalysis were measured, and the results are shown in the figure. Fig.11 As shown in the figure, it can be seen that before photocatalysis and after catalysis for 3 times, PCN-222 / Ag 3.0 / COF2 characteristic diffraction peaks did not change significantly. The results showed that PCN-222 / Ag 3.0 / COF2 has stable performance.
[0078] In particular, the experimental process was combined with XPS ( Fig.12 )、Uv-vis( Fig.13 )、MS( Fig.14 ) and other characterization methods were used to analyze the structural characteristics of the composite photocatalyst. The results showed that a special Z-type heterojunction was formed in the composite photocatalyst. This is because MOF and COF have matching energy band structures, which are conducive to the formation of a Z-type heterojunction with rapid charge transfer. The appearance of this structure plays an important role in promoting the degradation of oxytetracycline hydrochloride. This is because the appearance of this structure makes the electron conduction process inside the material fast and effective, and the recombination rate of photogenerated electrons is reduced, which greatly improves the efficiency of photocatalytic degradation. The XPS picture of the composite photocatalyst is shown below: Fig.12 As shown in the figure, Ag was detected in the PCN-222 / Ag / COF composite material, proving that Ag does exist in the material in the form of a single substance, and that the binding energy of the MOF and COF samples changed before and after the combination, and it was preliminarily inferred that electrons flowed from COF to MOF; the UV-vis graph of the composite photocatalyst, as shown in the figure Fig.13As shown, the MS image of the composite photocatalyst is Fig.14 In addition, through electrochemical characterization, it was analyzed that both PCN-222 and COF are p-type semiconductors, and the degradation mechanism diagram of PCN-222 / Ag / COF photodegradation of oxytetracycline hydrochloride was analyzed ( Fig.15 ).
[0079] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an Ag-modified MOFs@COFs composite photocatalyst, characterized in that: The steps include: S1. Dissolve zirconium oxychloride octahydrate and 4-carboxyphenylporphyrin in an organic solvent, carry out hydrothermal reaction at 130-150° C. for 48-72 hours in the presence of formic acid, and then wash and dry to obtain PCN-222; S2, dispersing the PCN-222 obtained in step S1 in water to obtain a PCN-222 dispersion; adding a silver nitrate solution to the PCN-222 dispersion, performing a photoreduction reaction under light conditions, and finally obtaining PCN-222 / Ag; S3, adding terephthalaldehyde and 1,3,5-tris(4-aminophenyl)benzene to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding acetic acid, reacting under stirring, and drying to obtain a covalent organic framework TAPB-PDA; adding different proportions of raw materials of the covalent organic framework TAPB-PDA and PCN-222 / Ag obtained in step S2 to a mixed solution of 1,4-dioxane and mesitylene, mixing evenly, adding different proportions of acetic acid, and after the reaction is completed, washing and drying to obtain PCN-222 / Ag / COF with different COF contents.
2. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: In step S2, the concentration of the PCN-222 dispersion is 2-3 g / L, the concentration of the silver nitrate solution is 0.1-0.2 mmol / L, the mass ratio of the PCN-222 content in the PCN-222 dispersion to the theoretical reduced Ag is 100:3; and the time of the photoreduction reaction is 3-4 h.
3. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: In step S1, the organic solvent is N,N-dimethylformamide, and the ratio of the mass of zirconium oxychloride octahydrate, the mass of 4-carboxyphenylporphyrin, and the volume of the organic solvent is 10:37.5:6.
5.
4. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: In step S1, the concentration of formic acid is 17.5-18 mol / L, and the ratio of its added volume to the mass of zirconium oxychloride octahydrate is 7:37.5; the temperature of the drying process is 120-130°C, and the time is 48-72h.
5. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: In step S3, the volume ratio of 1,4-dioxane to mesitylene in the mixed solution of 1,4-dioxane and mesitylene is 1:4; the ratio of the mass of terephthalaldehyde, the mass of 1,3,5-tris(4-aminophenyl)benzene to the volume of the mixed solution of 1,4-dioxane and mesitylene is 21 mg:42 mg:10 mL.
6. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: In step S3, the concentration of acetic acid is 0.5-0.6 mol / L; and the reaction time for preparing the covalent organic framework TAPB-PDA is 48-72 h.
7. The method for preparing the Ag-modified MOFs@COFs composite photocatalyst according to claim 1, characterized in that: The mass ratio of the covalent organic framework TAPB-PDA, the mass of PCN-222 / Ag and the volume ratio of the mixed solution of 1,4-dioxane and mesitylene is 53.55 mg:100 mg:10 mL; the reaction time is 48-72 h, and the temperature is 25-30 °C.
8. An Ag-modified MOFs@COFs composite photocatalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The composite photocatalyst is a rod-like structure, the main axis of the crystal is a hexahedron, the length is 25.11-43.64 μm, the particle size is 25.11-43.64 μm, the specific surface area is 115.44-118.50 m2 / g, and the average pore size is 0.1105-0.1165 mL / g.
9. Use of the Ag-modified MOFs@COFs composite photocatalyst according to claim 8 in photocatalytic degradation of oxytetracycline.
